THEORETICAL BASIS OF CREATION PROGRAMS PSYCHOLOGICAL REHABILITATION OF COMBATANTS WITH REMOTE CONSEQUENCES OF STRESS IMPACT - Popelushko, Roman (PSYCHOLOGICAL JOURNAL, 2016)
The article analyzes the theoretical and practical aspects of the program of psychological rehabilitation of combatants remote consequences of stress effects as actual problems of modern Ukraine. It is emphasized that there is necessity of creation comprehensive public system of social and psychological, social and vocational rehabilitation of combatants who take or took part in the hostilities, who had undergone combat mental and physical trauma, and allocation of them in a special group of social and psychological risk. Creating such a system will allow carry out targeted measures to secure physical and mental health of combatants will ensure prevention post-stress reactions and will promote psychological support and willingness of former military personnel of military formations to perform tasks in any conditions. The article aims to analyze the features creating a program of psychological rehabilitation of combatants remote consequences of stress influences. Based on the analysis of theoretical and practical fundamentals creating a program of psychological rehabilitation of combatants, remote consequences of stress influences, we made the following conclusion that the psychological rehabilitation of combatants should be carried out simultaneously in areas such, as: diagnosis the syndrome of social and psychological disadaptation in combatant; psychological counseling; psycho correction work; training in self-regulation; socio-psychological training; assistance in the professional self, career guidance. Attention is paid to the fact that further research should be directed to the study and improvement system of rehabilitation measures for the preservation of physical and mental health of combatants, prevention of post-stress reactions constructing of effective adaptation and rehabilitation systems, taking into account the personal characteristics combatant.